PERSEPSI MAHASISWA UNIVERSITAS RIAU TERHADAP PELAKSANAAN FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI RIAU 2014-2019 - Fauzi Fauzi; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by failure of Regional houseRepresentatives (DPRD) of Riau Province to carried out function of establi shing regional regulations, budgetary functions and supervisory func tions. This was indicated by existence of regional regulations that make it diffic ult for c ommunity, waste of budg et by regional government and DPRD. In addition, the f ollow up of cases pl ant waste was not responsive and other case s have caused reactions from community, especiall ystudents. In the student raises a reaction in the form of discussion, audience, carrying out demonstrations that indicate that there were injustice s and irregular ities felt by community. Therefore, the researcher raised the research entitled " The Perception of Riau University Students on Im plementation the Function of Regional House of Representatives (DPRD) of Riau Province 20 14 2019". The formulation of problem i nthis r esearch was how the Riau University Student's Per ception on Implementation the Functions of Regional house of Representatives of Riau Province. This research aim ed at knowing the Perception of Riau University Students on Implementation the Function of Regional H ouse of Representatives (DPRD) of Riau Province. 150 students were thesamples of this research that were taken by using purposive sampling technique, 15 repondents each faculty. The instruments of data collection that were done by using que stionnaires and interviews . 13 questions of question annire, 4 question for function offormation r egional regulations, 5 question s for budget functions, and 4 questions for supervisory functions. Based on the data analysis, student ’s percepti ons of impleme ntation the function of forming regional regulations were still considered good with percentage 74.17%, for budget function s it was considered good with percentage 70.13%, and for supervisory functions it was considered go od at 55.33%. The averageof three indicators above was 66.54%. A ccording to benchmark in the range 50.01% 75%. It can be concluded that the Perception of University Riau Student on the implementation of Functioning D PRD of Riau province was in Good category.Key Words : Students, Impl ementation of DPRD Function